2017
DOI: 10.1038/nature21393
|View full text |Cite
|
Sign up to set email alerts
|

Mediator structure and rearrangements required for holoenzyme formation

Abstract: The conserved Mediator co-activator complex has an essential role in the regulation of RNA polymerase II transcription in all eukaryotes. Understanding the structure and interactions of Mediator is crucial for determining how the complex influences transcription initiation and conveys regulatory information to the basal transcription machinery. Here we present a 4.4 Å resolution cryo-electron microscopy map of Schizosaccharomyces pombe Mediator in which conserved Mediator subunits are individually resolved. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
185
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(193 citation statements)
references
References 60 publications
(100 reference statements)
7
185
0
1
Order By: Relevance
“…We hypothesized that for protein complexes with a sufficient number of subunits and sufficiently distinct functional componentry, this modular structure may be reflected in the functional similarity networks. The Mediator complex is an evolutionarily conserved transcriptional activator composed of three stable modules – the Head, Middle and Tail (Figure 3A) – and one detachable, cell cycle specific module (Cyclin Kinase Module, not crystallized) (Nozawa et al, 2017; Tsai et al, 2017). Recent biochemical and genetic studies have demonstrated that the Head, Middle and Tail modules exhibit differential genomic targeting and have specialized roles in the context of Mediator complex global function (Jeronimo et al, 2016; Petrenko et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that for protein complexes with a sufficient number of subunits and sufficiently distinct functional componentry, this modular structure may be reflected in the functional similarity networks. The Mediator complex is an evolutionarily conserved transcriptional activator composed of three stable modules – the Head, Middle and Tail (Figure 3A) – and one detachable, cell cycle specific module (Cyclin Kinase Module, not crystallized) (Nozawa et al, 2017; Tsai et al, 2017). Recent biochemical and genetic studies have demonstrated that the Head, Middle and Tail modules exhibit differential genomic targeting and have specialized roles in the context of Mediator complex global function (Jeronimo et al, 2016; Petrenko et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…This density localizes near the region of attachment of the CAK subcomplex to the TFIIH core, as visualized in 2D class averages and 3D reconstructions of negatively stained TFIIH (Extended Data Fig. 8a–c and refs 6, 26), and reconstructions of TFIIH in the context of the assembled Pol II-PIC (see below and refs 5, 27). Previous data additionally show that MAT1 interacts with the XPD ARCH domain, and that the C259Y mutation in the ARCH domain impairs binding 28 .…”
mentioning
confidence: 91%
“…Recent cryo-EM studies using budding or fission yeast proteins have visualized the interaction of a partial or full TBP-based PIC with the large Mediator complex involved in gene-specific activation of transcription [3840]. Those studies have shed light on Mediator’s role in PIC stabilization and recruitment.…”
Section: Proposed Model For Tfiid Interaction With the Rest Of The Picmentioning
confidence: 99%
“…This model was generated by superposition of the common elements of three different cryo-EM structures – the human TFIID-TFIIA-promoter complex [25**], the human TBP-based PIC (including TBP, TFIIA, TFIIB, TFIIF, TFIIS, TFIIE, TFIIH, and Pol II) [32**], and the Mediator-Pol II complex from Schizosaccharomyces pombe [40**]. The resulting model represents an ~3 MDa transcription initiation supracomplex including TFIID, TFIIA, TFIIB, TFIIF, TFIIS, TFIIE, TFIIH, Pol II, and the Mediator coactivator complex.…”
Section: Figurementioning
confidence: 99%